Étude archéologique, micromorphologique et architecturale de deux bâtiments d’estive de l’époque moderne dans les Monts du Forez (Massif central, France) - Antoine Scholtes; Mireille Busseuil; Jacques Verrier; Priscille Chapuis; Hervé Cubizolle (Archéologie Médiévale)
Abstract: As part of the research developed around summer pasture dwellings in high Forez, agropastoral building techniques and arrangements during the second half of the medieval and the early modern periods (11th-18th c.) have been studied through archaeological prospections and surveys, as well as micromorphological analysis, revealing some of the materials used by agropastoral communities in construction. The results presented were collected during two separate campaigns on the early modern sites of Vieux-Colleigne and Barras.